The tax structure and the collection of the tax on industry and commerce in the Municipality of Cota - Cundinamarca (2018)
This essay is focused on the review and analysis of the tax structure and the collection behavior of the Industry and Commerce Tax in the municipality of Cota - Cundinamarca, during the 2015, 2016 and 2017 periods, establishing its structure and basic elements that make up said tax, for this, the budgetary executions of the municipality of the respective vigencias were taken as the basis for analysis. Likewise, the Tax Statute of the municipality and the fiscal performance indicators were reviewed to be able to determine the importance of the tax within the own revenues of the municipality and what is its percentage weight with respect to the different resources obtained by the Municipality